Service Quality and Students’ Satisfaction in Tanzania’s Higher Education: A Re-examination of SERVQUAL Model - Magasi, Chacha; Mashenene, Robert Galan; Ndengenesa, Dorice Munuo (International Review of Management and Marketing, 2022)
This study assessed the effect of service quality on customer satisfaction in Tanzanian’s higher education by re-examination of SERVQUAL Model through testing its existing five dimensions, namely; tangibles, reliability, responsiveness, empathy and assurance and one new suggested dimension, namely, compliance. The study was carried out in higher learning institutions situated in Dodoma city. The study employed a stratified random sampling technique to select a sample. The study adopted a cross-sectional research design whereas a questionnaire survey was used to collect quantitative data from a sample of 326 students from higher learning institutions. Descriptive statistics were used to compute the quality of services using perceived service quality (P) and expected service quality (E). Inferential statistics involved a binary logistic regression model to estimate the effect of service quality dimensions and compliance on customer satisfaction. The findings show that service quality in higher education was perceived by students to be below their expectations. The findings from logit model revealed that tangibles, reliability, responsiveness, empathy, assurance and compliance were important variables in predicting students’ satisfaction in higher education.